French Fiction, Empathy, and the Utopian Potential of 9/11 - Tim Gauthier (Studies in 20th & 21st Century Literature, 2013)
In From Solidarity to Schisms, Cara Cilano conceptualizes September 11 as a moment “characterized by unfathomable vulnerability and the possibility of a better future.” She argues the event, while traumatic, might have served as an impetus to reconfigure American self-perceptions and thoughts about its place in the world. Instead, she contends, the United States squandered the utopian potential of this moment. Cilano remains optimistic, however, because she sees European fictional discourse on 9/11 as emblematic of a desire for a melding of divergent perspectives. Their critique aims to keep America’s sense of itself unbalanced, thus providing fuel for self-reflection, analysis, and, most important, renewal. Taking the measure of current Franco-American relations, this essay tests the validity of this contention by examining works of French fiction published in the five years after the attacks. Four of these texts—Christian Garcin’s La jubilation des hasards, Didier Goupil’s Le jour de mon retour sur terre, Luc Lang’s 11 septembre, mon amour, and Frédéric Beigbeder’s Windows on the World—will be the focus of this essay. Are they being written to take advantage of the cosmopolitan potential of the moment, or grasping the opportunity to criticize a (weakened) nation, and thereby expressing uniquely French concerns? The essay contemplates the extent to which self-interest and questions of identity—personal, political, national—interfere with empathy, thus posing a considerable challenge to the utopian dream of a cosmopolitan world.
Keywords: From Solidarity to Schisms; Cara Cilano; September 11th; 9/11; American self-perception; United States; utopia; utopian; utopian dream; renewal; Franco-American; Christian Garcin; La jubilation des hasards; Didier Goupil; Le jour de mon retour sur terre; Luc Lang; 11 septembre; mon amour; Frédéric Beigbeder; Windows on the World; self-interest; questions of identity